2017
DOI: 10.1149/07801.1543ecst
|View full text |Cite
|
Sign up to set email alerts
|

Interconnect Corrosion in Steam Containing Fuel Gas

Abstract: Iron or chromium based alloys are currently the most preferred materials for SOFC interconnects. The poisoning of the cathode of the membrane electrode assembly (MEA) due to evaporation of chromium species from the metallic interconnect (MIC) and the oxidation of the interconnect surface during stack operation at elevated (800-900 °C) temperatures are regarded to be the major mechanisms affecting the degradation behaviour of the SOFC stack. The oxidation at the cathode side of the interconnect can cause up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Corrosion exposures in high steam content (90% H2O/10% H2) at 750 °C revealed that the uncoated Crofer 22 APU does not "survive" a 2000 h exposure to this environment. In literature, the number of publications investigating steel corrosion in gases with such a high steam content is limited [ [31,42]].…”
Section: Figurementioning
confidence: 99%
“…Corrosion exposures in high steam content (90% H2O/10% H2) at 750 °C revealed that the uncoated Crofer 22 APU does not "survive" a 2000 h exposure to this environment. In literature, the number of publications investigating steel corrosion in gases with such a high steam content is limited [ [31,42]].…”
Section: Figurementioning
confidence: 99%
“…In parallel degradation study (18) the interface between the CFY and the nickel mesh was investigated by dual gas samples with 4 probe resistance measurement at 875°C in 50% H 2 O in H 2 . The area specific resistance was ASR=1.2 mΩcm² after 100 h with minor increase of ∆ASR=0.4 mΩcm²/1000 h. Normed to the stack this value will be the half and have a negligible amount on the stack degradation (∆ASR=0.2 mΩcm²/1000 h).…”
Section: Ecs Transactions 78 (1) 3089-3102 (2017)mentioning
confidence: 99%